Treatment and recovery of phosphate from submerged anaerobic membrane bioreactor effluent using thermally treated biowaste and powder activated carbon - Photiou, Panagiota; Constantinou, Despina; Papaioakeim, Photini; Agapiou, Agapios; Vyrides, Ioannis (My University, 2024)
This study presents a novel treatment system using a submerged anaerobic membrane bioreactor (SAnMBR) followed by adsorption onto thermally treated biowaste, and ending with a final treatment using powdered activated carbon (PAC). Despite limited phosphate and ammonium ion removal during SAnMBR operation, thermally treated eggshell (EGSL) and seagrass (SG) received SAnMBR effluent and enhanced phosphate recovery, achieving removal rates of 71.8-99.9% and 60.5-78.0%, respectively. The SAnMBR achieved an 85% COD removal, which was slightly reduced further by biowaste treatment. However, significant further reductions in COD to 20.2 ± 5.2 mg/L for EGSL effluent and 57.0 ± 13.3 mg/L for SG effluent were achieved with PAC. Phytotoxicity tests showed the SAnMBR effluent after PAC treatment notably improved seed growth compared to untreated wastewater. In addition, volatile organic compounds (VOCs) were significantly reduced in the system, including common wastewater contaminants such as dimethyl disulfide, dimethyl trisulfide, phenol, p-cresol, nonanal, and decanal. Fractionation analysis of the solid fraction, post-adsorption from both synthetic and domestic wastewater, indicated that for SG, 77.3%-94% of the total phosphorus (TP) was inorganically bound, while for EGSL, it ranged from 94% to 95.3%. This study represents the first attempt at a proof-of-concept for simultaneous treatment of domestic wastewater and phosphorus recovery using this integrated system.
Keywords: Biowaste; Domestic wastewater treatment; PAC; Phosphate recovery; Αdsorption